The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/10916466.2011.596888
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Environmentally Friendly Production of Single Cell Protein From Petrochemical Wastewater Using a Halophilic Microorganism in Different Conditions

Abstract: In this study, biodegradation of petrochemical wastewater and production of single cell protein from it as carbon source was investigated using several process parameters. The process parameters such as carbon source, type of phosphorus source, phosphorus source concentration, type of nitrogen source, nitrogen source concentration, and temperature were considered. In order to investigate the influence of process parameters, a factorial design using Taguchi method was applied with six factors at four levels. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This biomass was used to feed rats [33]. Taran and Asadi (2014) showed that Haloarcula sp. IRU1 degrade petrochemical wastewater and use it as carbon source for single cell protein production in different conditions.…”
Section: Bacterial Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…This biomass was used to feed rats [33]. Taran and Asadi (2014) showed that Haloarcula sp. IRU1 degrade petrochemical wastewater and use it as carbon source for single cell protein production in different conditions.…”
Section: Bacterial Sourcesmentioning
confidence: 99%
“…IRU1 degrade petrochemical wastewater and use it as carbon source for single cell protein production in different conditions. They obtained SCP with 76.4% protein content [34]. Soya bean hull obtained from soya bean oil extraction is a cheap feed ingredient with a high fiber content.…”
Section: Bacterial Sourcesmentioning
confidence: 99%